Role of simile in the creation of a state’s image in English-Canadian poetry (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
One of the main stylistic means of imagery’s creation in literature is simile. This comparative figure of speech is for a long time in the limelight of linguists and specialists in literature and studied from the different approaches on the basis of various languages, in the works of different writers, poets etc., but in spite of this many problems in simile’s studying remains disputable or untouched upon. This article is devoted to study of the stylistic potential of simile as a means of creation of a state’s image in English-Canadian poetry of the XVIII-XXI centuries. Special attention in the article is drawn to the structural and semantic peculiarities of simile in analyzed poems. In modern linguistics there are numerous approaches to the structural classification of simile: in different philological researches there are different points of view about quantity of simile’s components, their number varies from two to five. But the majority of researchers of this stylistic device considers that it consists of at least three main components: a subject of comparison (comparandum), an object of comparison (comparatum) and a basis for comparison (tertium comparationis). Some linguists add to these basic components some extra ones. For example, to such extra component belong a comparative formant, which is usually a structural part of speech (conjunctions or prepositions), and a conclusion from a comparison, which is new information received in the result of simile. Their consideration allows to understand the inner meaning of simile better, so in this paper analyzing the instances of state’s simile in English-Canadian poetry we take into consideration all five components.The instances of the simile were also classified in accordance with the meaning of the object of comparison. It was determined in the research that the prevalent model of the state’s simile in English-Canadian poetry of the XVIII-XXI centuries is based on the comparison with an inanimate object. Herewith the basis for comparison in all cases differs. In the article we give the examples of the state’s comparison with such inanimate objects as a shield, a piece of paper, a paradise and a wind, explain the basis for comparison of these similes and make a conclusion from it.
Keywords: simile; a subject of comparison; an object of comparison; state’s image; English-Canadian poetry